Pengaruh Pengetahuan Keuangan Dan Sikap Keuangan Terhadap Perilaku Pengelolaan Keuangan Dengan Locus Of Control Sebagai Variabel Moderasi - Farda Putri Praditya; Kardiyem Kardiyem (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2023)
In the era of globalization and digitalization, people, especially Generation Z, easily make transactions without paying attention to priority scale. This leads to poor financial management behavior. This study aims to identify and analyze the impact of financial knowledge and financial attitudes on financial management behavior with a controlling focus as a moderating variable for economics education students Class of 2020 in Semarang City. The sample size was 219 respondents. Sampling technique uses proportional random sampling technique. The data collection method uses a closed-ended questionnaire. Data analysis techniques using descriptive analysis and SEM PLS. The results of hypothesis testing show that financial knowledge and financial attitudes have a positive and significant impact on financial management behavior, that locus of control is likely to enhance the influence of knowledge. financial awareness on financial management behavior and that locus of control has the potential to strengthen the influence of financial attitude on financial management behavior. The suggestion for further research is that students need to improve their financial knowledge and attitudes towards financial management to be able to manage their finances better.